Progress on application of dipeptidyl peptidase Ⅲ in the treatment of sepsis - WANG Yingchen, SUN Liqun (Jichu yixue yu linchuang, 2023)
Sepsis is still one of the important challenges of medicine in the 21st century. Dipeptide peptidase Ⅲ(DPP3)is a new biomarker associated with sepsis, which mainly degrades angiotensin Ⅱ in human body. It can not only inhibit cardiac systolic function, but also reduce vascular tension, resulting in insufficient cardiac output and low blood pressure, resulting in shock and multiple organ dysfunctions in patients with sepsis. Therefore, DPP3 may become a new target for sepsis treatment.